Divorce, remariage et condition juridique des femmes en Moldavie (xviie siècle-début du xixe siècle) - Elena Bedreag (Genre & Histoire)
Because of their consequences and their implications, both at the level of kinship structures and at the society level, divorces and remarriages, as indicators of social dynamism, constitute extremely important research subjects regarding family history. The present research is focused on Moldavia (the former historic province, bordered by the Carpathian Mountains to the West and the Dniester river to the East) mainly on the 17th and 18th centuries, but it also goes up to the beginning of the 19th century, that is to say until the Organic Regulations. The main objectives of the present study are to show how the orthodox divorce was managed: who coordinated, supervised and arranged the separation of the couple and what were the consequences of this. In addition to clarifying the context in which the separation occurs (who is seeking the divorce, what the reasons are) the present research intends to analyse the consequences of these divorces on family relations and dynamics. Besides the fact that the separation of couple could produce a series of complications inside the family, it also had financial consequences. Beyond the various reasons that led to divorce, the couple's split involved economic and patrimonial stakes.